IDENTIFIKASI PEMAHAMAN KONSEPTUAL DAN ALGORITMIK SISWA KELAS XI SMAN 4 BANDA ACEH PADA MATERI TERMOKIMIA TAHUN AJARAN 2014/2015 - Ade Ismayani; M. Hasan; Nuzulia ' (Jurnal Pendidikan Kimia Universitas Riau, 2016)
This study aims to identify the percentage of algorithmic and conceptual understanding on thermochemical lessons in the students of academic year of 2014/2015 grade XI SMAN 4 Banda Aceh. This study will contribute to determine the conceptual and algorithmic understanding of students, so that thermochemical lessons can use appropriate learning models in order to produce high level conceptual and algorithmic capabilities. A simple random sampling was used in this study, in which data was collected by using instrument tests: questionnairesand interviews. The research subjects were 50 students of class XI- IA SMAN 14. This study applied a descriptive quantitative method.. Based on the percentage of conceptual understanding and algorithmic derived on A1C1 was 8%, A1C0 was 4%, A0C1 was 20%, A0C0 was 0%, and there was 68% of students who have the algorithmic and conceptual understanding in the middle. This preliminary research is so significant for future research.